Molecular Survey of Enteric Viruses Associated with Poultry Enteritis in Southern Rajasthan, India - Saraswat, A.; Sharma, D. K.; Joseph, B.; Singathia, R.; Patidar, C. (International Journal of Livestock Research, 2021)
Enteric viruses play major role in affecting the poultry industry worldwide, the occurrence of enteric viruses in poultry is still very poorly explored in India. Therefore, a molecular survey has been performed to determine the presence of enteric viruses among enteritis affected poultry flocks of Udaipur and Chittorgarh districts of Southern Rajasthan, India. Total 60 pooled samples of intestine were collected from enteritis affected dead birds, DNA and RNA viruses were detected by PCR and reverse transcriptase PCR respectively. Enteric viruses namely Fowl adenovirus-I(FADV-I), Chicken parvovirus (CPV), Avian coronavirus (ACV), and Chicken astroviruses (CAstV) were detected in 73.32 % of investigated samples. FAdV-I (21.66%) was detected as highest single virus infection followed by ACV (13.33%). Combinations of two or more enteric viruses were simultaneously identified in 38.33% samples.